Resistance of Kansas Sclerotinia homoeocarpa isolates to thiophanate-methyl and determination of associated β-tubulin mutation - Ostrander, Jesse C.; Todd, Richard B.; Kennelly, Megan M. (My University, 2014)
Eighty-two isolates of Sclerotinia homoeocarpa from 12 sites in Kansas were evaluated for in vitro sensitivity to the methyl benzimidazole carbamate (MBC) fungicide thiophanate-methyl at the discriminatory dose of 10 μg/ml. Seventeen isolates were sensitive to thiophanate-methyl and the remaining isolates were resistant. Of the 65 isolates from golf course putting greens, two isolates were sensitive and the remaining 63 isolates were resistant. Six resistant and five sensitive isolates were also evaluated in greenhouse assays on fungicide-treated plants. The isolates that were sensitive to thiophanate-methyl in vitro did not cause any disease on thiophanate-methyl-treated plants, and those that were resistant in vitro caused blighting on treated plants equivalent to the nontreated controls. The entire β-tubulin gene was sequenced for four resistant and four sensitive isolates. The resistant isolates all harbored a substitution of alanine for glutamic acid at codon 198 (E198A). These results provide a starting point for further surveys and monitoring of fungicide sensitivity.
Citation: Ostrander, J., Todd, R., & Kennelly, M. (2014). Resistance of Kansas Sclerotinia homoeocarpa Isolates to Thiophanate-Methyl and Determination of Associated β-Tubulin Mutation. Plant Health Progress, 15(2), 23-27. https://doi.org/10.1094/PHP-RS-13-0120.